Modified calcium carbonate powder applied to silicone adhesive and preparation method thereof
By modifying heavy calcium carbonate powder and combining the use of specific additives, the problems of low whiteness and high cost of calcium carbonate powder in the prior art are solved, and the preparation of high-grade silicone glue is realized, and the dispersion and extrusion of the powder are improved.
Patent Information
- Application Number
- CN202411858032.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
AI Technical Summary
In the prior art, calcium carbonate powder used in silicone glue has problems such as low whiteness, high cost, weak lipophilicity, large bulk density and high oil absorption value, which is difficult to meet the use needs of high-end silicone glue.
Heavy calcium carbonate powder is used to modify it with specific additives (such as N,N'-ethylene bisstearamide, glycerin, aluminate coupling agent, castor oil derivative, dispersant and rheological agent). By adjusting the ratio and process steps, the whiteness, lipophilicity and dispersion of the calcium carbonate powder are improved.
The modified calcium carbonate powder has high whiteness, low cost, strong lipophilicity, low bulk density and low oil absorption value. It is suitable for the preparation of high-end silicone glue, and improves the dispersion and extrusion properties of silicone glue.
Smart Images

Figure CN119684819A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of calcium carbonate powder modification, in particular to a modified calcium carbonate powder applied to silicone glue, and also to a preparation method of the modified calcium carbonate powder. Background Art
[0002] Due to its low cost, easy coloring, high whiteness, low hardness, excellent chemical stability, thermal stability and non-toxicity, calcium carbonate has been widely used in papermaking, plastics, foam stabilizers, asphalt, films, rubber, coatings and other industries. Calcium carbonate is divided into light calcium carbonate and heavy calcium carbonate. Light calcium carbonate has the characteristics of large specific surface area, uniform particle size and shape, and has been widely used in silicone adhesives, among which nano calcium carbonate is particularly widely used in silicone adhesives.
[0003] For example, in the patent document with the application number CN201810292424.8 and the name "A method for preparing nano calcium carbonate for silicone adhesive", the process adopted is to carbonize the refined slurry, add a zinc chloride solution with a calcium carbonate mass of 0.5-1.0% to the carbonized slurry, grind the calcium carbonate slurry, add a mixed saponification liquid of fatty acid and diethylenetriamine pentaacetic acid iron-sodium complex to the ground slurry, and control the temperature of the coating liquid at 70°C to 75°C under the action of a homogenizing pump, so that the dispersion and surface coating of calcium carbonate are completed simultaneously, and the coated slurry is filtered to a water content of 100%. The filter cake is less than 40%, and then the filter cake is dried to a moisture content of ≤0.3%, and a nano calcium carbonate product for silicone sealant is obtained; the patent document with the published application number CN202310177727.6 and the name "A preparation method of nano calcium carbonate for flame retardant silicone sealant" discloses a preparation method including a calcination process, a digestion process, a slag removal process, a concentration adjustment process, a carbonization process and a dehydration and drying process. The specific scheme is to reduce the oil absorption value of calcium carbonate by sodium palmitate when preparing nano calcium carbonate, thereby improving the extrudability of the flame retardant silicone sealant and improving the elongation of the flame retardant silicone sealant. The flame retardant silicone sealant uses nano calcium carbonate to facilitate the elongation of the sealant and avoid the phenomenon of tearing the sealant when the building materials vibrate, thereby improving the stability of the sealant and helping to ensure the safety of the building. In both of the above schemes, light calcium carbonate is used. The environmental protection issues in the technology need to be discussed, and the environmental protection issues will lead to a substantial increase in costs. The cheap heavy calcium carbonate is only used as a component for adjusting the fluidity of silicone glue and is only used in a small amount in the preparation of silicone glue.
[0004] In the invention patent with patent number CN202110349887.5 and name "A method for preparing heavy calcium carbonate for highly activated silicone adhesive", although relatively cheap heavy calcium carbonate is used as the active heavy calcium carbonate for preparing silicone adhesive, the powder used is only 1250 mesh, which makes it difficult to achieve large filling amounts and the stability of the finished adhesive is difficult to ensure, especially it cannot meet the use requirements of high-end silicone adhesive preparation. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a modified calcium carbonate powder for silicone adhesive which has high whiteness, low cost, strong lipophilicity, low bulk density and low oil absorption value.
[0006] In order to solve the above technical problems, the technical solution of the present invention is: modified calcium carbonate powder applied to silicone adhesive, including heavy calcium carbonate powder and an additive for modifying the heavy calcium carbonate powder;
[0007] The additives include N,N′-ethylenebisstearamide, glycerol, an aluminate coupling agent, a castor oil derivative, a dispersant and a rheological agent;
[0008] The mass ratio of the heavy calcium carbonate powder and the additive is: 100 parts of the heavy calcium carbonate, 0.3-0.5 parts of the N,N′-ethylenebisstearamide, 0.2-0.35 parts of the glycerol, 0.8-1.5 parts of the aluminate coupling agent, 0.7-1.0 parts of the castor oil derivative, 0.3-0.7 parts of the dispersant, and 0.5-0.8 parts of the rheological agent.
[0009] As a preferred technical solution, the castor oil derivative is one of maleic ricinoleic acid polyethylene glycol ester, castor oil-based water-based compounds, multifunctional castor oil-based polyurethane acrylate, and epoxy castor oil; wherein the structural formula of maleic ricinoleic acid polyethylene glycol ester is,
[0010]
[0011] Where n is 10, 15 or 20;
[0012] The structural formula of the castor oil-based aqueous compound is,
[0013]
[0014] The structural formula of the multifunctional castor oil-based polyurethane acrylate is:
[0015]
[0016] The structural formula of the epoxy castor oil is:
[0017]
[0018] As a preferred technical solution, the dispersant is a comb-shaped hyperdispersant;
[0019] The comb-shaped hyperdispersant is one of a polyetheramine grafted polycaprolactone comb-shaped hyperdispersant, a polyamideamine grafted polycaprolactone comb-shaped hyperdispersant, and an amine-terminated "comb-shaped" polycaprolactone hyperdispersant;
[0020] Wherein, the structural formula of the polyetheramine grafted polycaprolactone comb-shaped hyperdispersant is:
[0021]
[0022] Where m:n is 1:0.7 or 1:0.8;
[0023] The structural formula of the polyamidoamine grafted polycaprolactone comb-shaped hyperdispersant is:
[0024]
[0025] Where p is 5, 10 or 15;
[0026] The structural formula of the amine-terminated "comb-shaped" polycaprolactone hyperdispersant is:
[0027]
[0028] Where n is 12 to 25.
[0029] As a preferred technical solution, the rheological agent is one of polyamide wax, organic bentonite, and fumed silica, or a combination of the two in any ratio.
[0030] The present invention also relates to a method for preparing the modified calcium carbonate powder used in silicone glue, comprising the steps of processing and crushing the calcium carbonate ore raw material, grinding and grading, online particle size detection, powder modification and modified powder inspection.
[0031] As a preferred technical solution, the processing and crushing steps include:
[0032] SP A1 , Cleaning of ore raw materials
[0033] The calcium carbonate ore raw material is washed with tap water to remove the silt and humus in the ore raw material;
[0034] SP A2 , Sorting of ore raw materials
[0035] Manually sort out and remove the miscellaneous colored ores that affect the white hue in the ore raw materials;
[0036] SP A3 , Crushing of ore raw materials
[0037] The ore raw materials are crushed by a jaw crusher, and after two consecutive crushing processes, the ore raw materials are crushed into crushed ore with a maximum size not exceeding 30mm.
[0038] As a preferred technical solution, in the grinding and classification step, the crushed ore is ground by a vertical mill, and a grinding aid of 1 to 1.5‰ of the mass of the crushed ore is added during the grinding to obtain heavy calcium carbonate powder;
[0039] The grinding aid is one of sodium methyl ricinoleate sulfonate, sodium oleyl alcohol sulfonate and sodium acrylate;
[0040] The particle size of the heavy calcium carbonate powder tested by Malvern particle size tester is D 50 ≦1.55μm, D 97 ≦12.00μm.
[0041] As a preferred technical solution, the heavy calcium carbonate powder is classified, and the particle size of the heavy calcium carbonate powder selected after classification is 1.25 μm≦D tested by Malvern particle size tester. 50 ≦1.35μm, 3.80μm≦D 97 ≦4.00μm.
[0042] As a preferred technical solution, the grinding and classification step includes the following steps:
[0043] SP B1 1. Add 20 to 25 times the mass of distilled water to the grinding aid to dilute the grinding aid or make the grinding aid into an emulsion for standby use;
[0044] SP B2 , will be through SP A3 The crushed ore obtained in the step is evenly transported to the vertical mill, and a metering pump is used to transfer the SP B1 The treated grinding aid is sprayed onto the surface of the crushed ore in a mass ratio matching the mass ratio of the conveyed crushed ore;
[0045] SP B3 , grinding the crushed ore added with the grinding aid by a vertical mill to obtain heavy calcium carbonate powder;
[0046] SP B4During the grinding process, the heavy calcium carbonate powder with large calcium carbonate particles enters the coarse classifier, and the coarse classifier separates the heavy calcium carbonate powder from the large calcium carbonate particles. The separated heavy calcium carbonate powder enters the trap, and the separated large calcium carbonate particles return to the vertical mill for further grinding; the heavy calcium carbonate powder is sampled online before entering the trap and the particle size is detected, and the grinding process parameters of the vertical mill are adjusted according to the detection results until the particle size range of the ground heavy calcium carbonate powder is D 50 ≦1.55μm, D 97 ≦12.00μm;
[0047] SP B5 , particle size D 50 ≦1.55μm, D 97 The heavy calcium carbonate powder with a particle size of ≦12.00 μm enters the trap for classification, online sampling is performed for particle size detection, and the air flow introduced into the trap is adjusted until the particle size of the classified heavy calcium carbonate powder is D 50 ≦1.55μm, D 97 ≦10.00μm, the particle size is D 50 ≦1.55μm, D 97 Heavy calcium carbonate powder with a particle size of ≦10.00μm is introduced into the first fine-grained classifier, and the remaining heavy calcium carbonate powder after classification is introduced into the finished product bin. The heavy calcium carbonate powder introduced into the finished product bin is used as a filler in the production of pipes and rolled plates;
[0048] SP B6 , the particle size introduced into the subdivision classifier is D 50 ≦1.55μm, D 97 The heavy calcium carbonate powder with a particle size of ≦10.00μm is further classified, and online sampling is performed for particle size detection, and the air flow rate introduced into the subdivision classifier is adjusted until the particle size D is obtained. 50 ≦1.40μm, D 97 ≦6.00μm heavy calcium carbonate powder, particle size D 50 ≦1.40μm, D 97 Heavy calcium carbonate powder with a particle size of ≦6.00μm is continuously introduced into the second sub-classifier, and the remaining heavy calcium carbonate powder after classification is introduced into the finished product bin. The heavy calcium carbonate powder introduced into the finished product bin is used as filler for modified plastics and rubber;
[0049] SP B7 , the particle size introduced into the second subdivision classifier is D 50 ≦1.40μm, D 97 The heavy calcium carbonate powder with a particle size of ≦6.00μm continues to be classified, and online sampling is performed for particle size detection, and the air flow rate introduced into the second sub-classifier is adjusted until the particle size D is obtained. 50 >1.15μm, D97 >3.00μm calcium carbonate powder, D 50 >1.15μm, D 97 Heavy calcium carbonate powder with a particle size of >3.00μm is continuously introduced into the third sub-classifier, and the remaining heavy calcium carbonate powder after classification is introduced into the finished product bin. The heavy calcium carbonate powder introduced into the finished product bin is used for filling paint and ink;
[0050] SP B8 , the particle size D 50 >1.15μm, D 97 The heavy calcium carbonate powder with a diameter of >3.00μm continues to be classified, and online sampling is performed for particle size detection, and the air flow rate introduced into the subdivision classifier 3 is adjusted until the particle size of the classified powder is 1.25μm≦D 50 ≦1.35μm, 3.80μm≦D 97 Heavy calcium carbonate powder ≦4.00μm, the remaining heavy calcium carbonate powder after classification is introduced into the finished product warehouse, and the heavy calcium carbonate powder introduced into the finished product warehouse is used as filler for plastic modification.
[0051] As a preferred technical solution, the modification of the heavy calcium carbonate powder is prepared by using a first weightless mixer, a second weightless mixer and two sets of metering pump metering feeding devices with heater functions, including the following steps:
[0052] SP C1 , raising the temperature of the zero-gravity mixer to 90-95° C. and keeping the temperature for 30 minutes; passing cooling water through the zero-gravity mixer;
[0053] SP C2 , placing the castor oil derivative in a heater of a metering pump metering feeding device to heat the castor oil derivative to reduce the viscosity of the castor oil derivative, and the heating temperature of the heater is controlled at 70-90° C.;
[0054] SP C3 , heating the glycerin in a heater of another set of the metering pump metering feeding device to reduce the viscosity of the glycerin, and controlling the heating temperature of the heater to be 50-60° C.;
[0055] SP C4 , will be through SP B8 The heavy calcium carbonate powder prepared in the step is measured and poured into the zero-gravity mixer 1, and the zero-gravity mixer 1 is started to stir the heavy calcium carbonate powder, and the stirring speed of the zero-gravity mixer 1 is 50-70 rad / min;
[0056] SP C5, while the zero-gravity mixer is stirring, uniformly adding the dispersant weighed according to the ratio into the zero-gravity mixer, and the adding time is controlled within 30 to 45 seconds;
[0057] SP C6 2. When the temperature of the heavy calcium carbonate powder mixed with the dispersant in the zero-gravity mixer 1 reaches 90° C., the aluminate coupling agent weighed according to the ratio is evenly and slowly added into the zero-gravity mixer 1, and the adding time is controlled within 30 to 60 seconds;
[0058] SP C7 10 minutes after adding the aluminate coupling agent, C2 The castor oil derivative heated and reduced in viscosity is uniformly sprayed into the zero-gravity mixer 1 by using the metering pump metering feeding device, and the spraying time is controlled to be completed within 45 to 60 seconds;
[0059] SP C8 1 minute after the spraying of the castor oil derivative is completed, C3 The heated and viscosity-reduced glycerin is uniformly sprayed into the zero-gravity mixer 1 by using the metering pump metering feeding device, and the spraying time is controlled to be completed within 30 to 45 seconds;
[0060] SP C9 1 minute after the glycerol is sprayed, N,N′-ethylenebisstearamide weighed according to the ratio is uniformly added into the zero-gravity activation machine 1, and the adding time is controlled to be completed within 30 to 45 seconds;
[0061] SP C10 , the zero-gravity mixer continues stirring and heating for 20 to 25 minutes;
[0062] SP C11 , uniformly and slowly add the rheological agent weighed according to the ratio, the adding time is controlled to be completed within 45 to 60 seconds, and continue stirring for 3 to 5 minutes;
[0063] SP C12 , will be through SP C11 The material obtained by stirring in step 2 is discharged into the second weightless mixer, and stirred at a speed of 50 to 70 rad / min until the material is cooled to room temperature to obtain modified heavy calcium carbonate;
[0064] SP C13 , using a natural density meter to measure the bulk density of the modified heavy calcium carbonate, the bulk density is ≤ 0.45 g / cm 3The contact angle of the modified heavy calcium carbonate is measured by a contact angle meter, and the contact angle is ≧125°. The Hunter whiteness of the modified heavy calcium carbonate is measured by a whiteness meter, and the Hunter whiteness is ≧97%. The activation degree and oil absorption value of the modified heavy calcium carbonate are measured according to GB / T19281-2014 "Analysis Method of Calcium Carbonate", and the activation degree is ≧95%, and the oil absorption value is ≦12.5g / 100g. The modified heavy calcium carbonate is qualified;
[0065] SP C14 , the modified heavy calcium carbonate that passes the test is packaged into finished products.
[0066] Due to the adoption of the above technical solution, the present invention has the following beneficial effects:
[0067] ① In the present invention, the auxiliary agent glycerol, the aluminate coupling agent, and the castor oil derivative contain hydroxyl (-OH), alkoxy (-OR), amine (-NH 2 ), epoxy These groups can react with the hydroxyl (-OH) on the surface of the heavy calcium carbonate or produce hydrogen bonds under appropriate conditions, and produce chemical or physical bonds with the matrix material, ultimately improving the mechanical properties of the modified heavy calcium carbonate application.
[0068] ② In the present invention, the glycerol, the castor oil derivative, and the dispersant are all long-chain macromolecular additives and contain hydroxyl (-OH) or amine (-NH 2 ), when it is dissolved in an organic system, it gels due to hydrogen bonding to form a thixotropic network structure, and the long chains are swollen and entangled with each other; the rheological agent contains hydroxyl (-OH) and / or amide (-CONH 2 ), the molecules form a network structure due to the strong hydrogen bonding effect. These network structures or the long chains entangled with each other are destroyed under the action of shear force, which manifests as a decrease in viscosity, allowing the system to restore good fluidity. When the shear force is eliminated, the three-dimensional structure will recover by itself, and the viscosity will increase, which manifests as thixotropy.
[0069] ③ In the present invention, the composite additives are used in combination to form a hydrophobic oil film on the surface of the heavy calcium carbonate. At the same time, the use of the N,N'-ethylenebisstearamide, the glycerol, the castor oil derivative and the dispersant separates the distance between the heavy calcium carbonate powders, so that the heavy calcium carbonate modified by the present invention has excellent dispersibility and good extrusion properties when used in the production of silicone glue.
[0070] ④ In the present invention, the auxiliary agents are added sequentially, which maximizes the realization of the functions of the auxiliary agents. At the same time, the auxiliary agents are added sequentially, which avoids mutual influence and interference between the auxiliary agents.
[0071] ⑤ The heavy calcium carbonate powder separated by multiple grading can still be sold normally on the market, which will not cause waste in powder grading and increase in costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0072] The following drawings are only intended to illustrate and explain the present invention, and are not intended to limit the scope of the present invention.
[0073] in:
[0074] Figure 1 This is a simplified schematic diagram of the classification and screening of heavy calcium carbonate powder according to an embodiment of the present invention;
[0075] Figure 2 It is a schematic diagram of the rheological mechanism of organobentonite;
[0076] Figure 1 In: 1-air supply duct 1; 2-powder conveying duct 1; 3-coarse classifier; 4-powder recovery duct 1; 5-powder conveying duct 2; 6-catchpot; 7-powder recovery duct 2; 8-air supply duct 2; 9-powder conveying duct 3; 10-fine classifier 1; 11-powder recovery duct 3; 12-air supply duct 3; 13-powder conveying duct 4; 14-fine classifier 2; 15-powder recovery duct 4; 16-air supply duct 4; 17-powder conveying duct 5; 18-powder conveying duct 6; 19-fine classifier 3; 20-powder recovery duct 5. DETAILED DESCRIPTION
[0077] The present invention is further described below in conjunction with the accompanying drawings and examples. In the following detailed description, certain exemplary embodiments of the present invention are described only by way of illustration. Needless to say, those of ordinary skill in the art will recognize that the described embodiments may be modified in various ways without departing from the spirit and scope of the present invention. Therefore, the drawings and description are illustrative in nature and are not intended to limit the scope of protection of the claims.
[0078] The modified calcium carbonate powder used for silicone glue includes heavy calcium carbonate powder and an additive for modifying the heavy calcium carbonate powder. The additive includes N,N′-ethylenebisstearamide, glycerol, an aluminate coupling agent, a castor oil derivative, a dispersant and a rheological agent. Specifically, the mass ratio of the heavy calcium carbonate powder and the additive is 100 parts of the heavy calcium carbonate, 0.3 to 0.5 parts of the N,N′-ethylenebisstearamide, 0.2 to 0.35 parts of the glycerol, 0.8 to 1.5 parts of the aluminate coupling agent, 0.7 to 1.0 parts of the castor oil derivative, 0.3 to 0.7 parts of the dispersant, and 0.5 to 0.8 parts of the rheological agent.
[0079] The castor oil derivative is one of maleic ricinoleic acid polyethylene glycol ester, castor oil-based water-based compounds, multifunctional castor oil-based polyurethane acrylate, and epoxy castor oil. The structural formula of the maleic ricinoleic acid polyethylene glycol ester is:
[0080]
[0081] Where n is 10, 15 or 20.
[0082] The structural formula of the castor oil-based aqueous compound is,
[0083]
[0084] The structural formula of the multifunctional castor oil-based polyurethane acrylate is:
[0085]
[0086] The structural formula of the epoxy castor oil is:
[0087]
[0088] The mechanism of action of castor oil derivatives is as follows: ① Under the influence of long-term geological environment, calcium carbonate ore contains a large amount of bound water. During the grinding process, calcium carbonate ore dissociates, exposing unsaturated particles Ca 2+ and CO 3 2- , unsaturated particle Ca 2+ and CO 3 2- The unsaturation degree is very high and the activity is very strong. It is hydrolyzed with calcium carbonate combined with water, thereby forming a large number of hydroxyl groups (-OH) on the surface of calcium carbonate powder. The castor oil derivative structure contains hydroxyl groups (-OH), amino groups (-NH 2 ) or epoxy Among them, epoxy In the alkaline environment of calcium carbonate combined with water (pH value is about 10), the ring opens to produce hydroxyl (-OH). These highly active hydroxyl (-OH), amine (-NH 2 ) or epoxy The hydroxyl (-OH) generated by the ring opening reacts with the hydroxyl (-OH) on the surface of calcium carbonate under the dual effects of high temperature and shear, thereby forming a strong bond, thereby improving the performance of heavy calcium carbonate in silicone adhesives; ② The castor oil derivatives are all long-chain structure compounds. When applied to silicone adhesives, these long-chain structures are swollen and entangled with each other to form a network structure. At the same time, these castor oil derivatives contain hydroxyl (-OH) and / or amine (-NH 2), these hydroxyl (-OH) and / or amine (-NH 2 ) part is combined with the hydroxyl (-OH) on the surface of the heavy calcium carbonate powder, and the remaining hydroxyl (-OH) and / or amine (-NH 2 ) forms a network structure through hydrogen bonds. When sheared, the entangled molecular chains are pulled apart and the viscosity decreases. When the shear stops, the macromolecular chains are entangled again and the viscosity increases, thus having the thixotropy required by silicone glue.
[0089] The dispersant is a comb-shaped hyperdispersant. The comb-shaped hyperdispersant is one of a polyetheramine grafted polycaprolactone comb-shaped hyperdispersant, a polyamideamine grafted polycaprolactone comb-shaped hyperdispersant, and an amine-terminated "comb-shaped" polycaprolactone hyperdispersant. The structural formula of the polyetheramine grafted polycaprolactone comb-shaped hyperdispersant is:
[0090]
[0091] Where m:n is 1:0.7 or 1:0.8.
[0092] The structural formula of the polyamidoamine grafted polycaprolactone comb-shaped hyperdispersant is:
[0093]
[0094] Where p is 5, 10 or 15.
[0095] The structural formula of the amine-terminated "comb-shaped" polycaprolactone hyperdispersant is:
[0096]
[0097] Where n is 12 to 25.
[0098] Dispersing mechanism of the dispersant: This embodiment uses a polyetheramine grafted polycaprolactone comb-like hyperdispersant, a polyamideamine grafted polycaprolactone comb-like hyperdispersant or an amine-terminated "comb-like" polycaprolactone comb-like hyperdispersant. All three use polycaprolactone as the solvating segment, and polyetheramine, polyamideamine or polyethylene polyamine as the anchoring group. The anchoring group is mainly combined with the surface of the powder particles through ionic bonds, hydrogen bonds and van der Waals forces, adsorbed on the surface of the particles, and forms an adsorption layer around the particles, which is not easy to desorb; the solvated chain forms a coating layer on the surface of the particles. According to the three-dimensional (spatial) stabilization mechanism, when two particles adsorbed with hyperdispersant molecules are close to each other and the distance between them is less than 2 times the thickness of the adsorption layer, the steric hindrance generated by the extended solvated chain causes the particles to bounce off and prevent them from agglomerating. At the same time, the hyperdispersants selected by the present invention are all long-chain structure compounds, and their structures contain hydroxyl groups (-OH) and / or amine groups (-NH 2 ) and other groups, so it has the same thixotropic function in silicone rubber as the castor oil derivative.
[0099] The rheological agent is one of polyamide wax, organic bentonite, fumed silica, or a combination of two of them in any ratio. The mechanism of action of the rheological agent is:
[0100] ① The polyamide wax molecular chain contains hydroxyl (-OH) and amide (-CONH 2 ), the molecules form a network structure due to the strong hydrogen bonding, which provides thixotropy for the system.
[0101] ② When organic bentonite is dispersed in an organic system, its rheological mechanism in an organic solvent system is as follows: Figure 2 (Source: Wang Chunwei. Characteristics and Application of Bentonite Thickening Rheological Agent [J]. Coatings Industry, 1999, (12): 18-20.) Organic bentonite usually does not exist as primary particles, but is generally agglomerates of multiple particles. Primary particles can be produced through the wetting, dispersion and activation process, forming an efficient thixotropic effect. In addition to providing chemical energy to help the organic bentonite disperse, the water contained in the organic solvent migrates to the hydroxyl groups at the edge of the bentonite flakes to form hydrogen bonds. Through the bridging of water molecules, countless bentonite flakes form a gel structure, and the hydrocarbon chains on the flake surface fix the solvent through their strong solvation ability, thereby thickening the system and producing a thixotropic effect. Under the action of external force, this structure is destroyed and the viscosity is reduced. When the external force is removed, it returns to its original structure and viscosity within a certain period of time.
[0102] ③ The surface of fumed silica has many highly active silanol groups (Si-OH). The hydrogen bonding of the surface silanol groups (Si-OH) can make the silica aggregates dispersed in the system form a complete silica network that fills the entire system, increasing the viscosity of the system and thus playing a thickening role. When an external force acts on the system, the hydrogen bonds break and the silica network is destroyed, causing the viscosity of the system to decrease under the action of shear force; once the shear force disappears, the silica network can be formed again, and the viscosity of the system returns to its original state, thus reflecting thixotropy.
[0103] The coupling mechanism of the aluminate coupling agent is as follows: the easily hydrolyzed alkoxy group (-OR) in the aluminate coupling agent is hydrolyzed into a hydroxyl group (-OH) under the action of calcium carbonate combined water, and chemically reacts with the hydroxyl group (-OH) on the surface of calcium carbonate under high temperature and shear force to form an irreversible AL-O bond, and the organic long molecular group at the other end can be chemically cross-linked and physically entangled with the matrix molecular chain, thereby significantly improving the processing performance and physical and mechanical properties of the product.
[0104] The mechanism of action of the glycerol is as follows: the glycerol molecular chain contains hydroxyl groups (-OH), which can react chemically with the hydroxyl groups (-OH) on the surface of the heavy calcium carbonate under high temperature and shear force to form -O- bonds, thereby firmly linking with the heavy calcium carbonate. At the same time, glycerol is a long alkane compound. When applied to silicone glue, these long chain structures are swollen and entangled with each other to form a network structure. The hydroxyl groups (-OH) form a network structure through hydrogen bonds, thereby having the same thixotropy as the castor oil derivative.
[0105] The lubricating and anti-adhesive effects of the N,N′-ethylenebisstearamide are well-known technologies and will not be described in detail here.
[0106] The aluminate coupling agent, the glycerol and the castor oil derivative are all organic substances, and can form an organic monomolecular oil film on the surface of calcium carbonate when combined.
[0107] The glycerol, the castor oil derivative and the comb-shaped hyperdispersant cooperate with each other, and the network structure formed by the mutual entanglement between the macromolecular chains and the above-mentioned compounds and the rheological agent contain a large number of hydroxyl (-OH) or amine (-NH 2 ), amide group (-CONH 2 ) and other groups, the network structure formed by the strong hydrogen bonding between molecules, provides a modified heavy calcium carbonate system for the thixotropy of silicone rubber.
[0108] The preparation method of modified calcium carbonate powder applied to silicone rubber in this embodiment includes the steps of processing and crushing calcium carbonate ore raw materials, grinding and grading steps, online particle size detection steps, powder modification steps and modified powder inspection steps.
[0109] Wherein, the processing and crushing steps include:
[0110] SP A1 , Cleaning of ore raw materials
[0111] The calcium carbonate ore raw materials are washed with tap water to remove the mud and humus in the ore raw materials.
[0112] SP A2 , Sorting of ore raw materials
[0113] The mixed colored ores that affect the white hue in the ore raw materials are manually sorted and removed.
[0114] SP A3 , Crushing of ore raw materials
[0115] The ore raw materials are crushed by a jaw crusher, and after two consecutive crushing processes, the ore raw materials are crushed into crushed ore with a maximum size not exceeding 30mm.
[0116] The purpose of cleaning and sorting the ore raw materials is to prevent the silt, humus and mixed colored ore from affecting the stability of the powder hue and whiteness. The ore raw materials are crushed into broken ore with a maximum size of no more than 30mm in this step, which can prevent fluctuations in the grinding process due to ore size being too large or too small, and avoid affecting the stability and consistency of the powder particle size.
[0117] In the grinding and classification step, the crushed ore is ground by a vertical mill to obtain heavy calcium carbonate powder. The particle size of the heavy calcium carbonate powder tested by a Malvern particle size tester is D 50 ≦1.55μm, D 97 ≦12.00μm. In this embodiment, the heavy calcium carbonate powder is classified, and the particle size of the heavy calcium carbonate powder selected after classification is 1.25μm≦D tested by Malvern particle size tester 50 ≦1.35μm, 3.80μm≦D 97 ≦4.00μm.
[0118] In this embodiment, a grinding aid of 1-1.5‰ of the mass of the crushed ore needs to be added during the grinding process. The grinding aid is one of sodium methyl ricinoleate sulfonate, sodium oleyl alcohol sulfonate, and sodium acrylate. The grinding aid mechanism of the grinding aid is that the grinding aid is adsorbed on the new surface of the stone when the ore is ground, reducing the external stress required for crack expansion when the particles are broken, and promoting the expansion of the cracks. With the increase of the specific surface area and specific surface energy of the particles, the bond force between adjacent atoms is broken, and this bond force is naturally activated on the new surface formed after the crushing. Due to the initial stage of crushing, the new surface tends to be generated along the original fine cracks or strength weakening parts inside the particles, and the bond force on the new surface is small. With the extension of the crushing time and the reduction of the particle size, the unsaturation degree on the new surface will gradually increase. The increase of its surface energy and the mechanical activation effect make the added product spontaneously perform physical adsorption and chemical adsorption on the new surface, among which the chemical adsorption effect is more prominent. Since the adsorption of these molecules reduces the surface energy and generates steric hindrance, it can prevent the aggregation and recrystallization between particles, and play a role in dispersion and grinding.
[0119] The grinding and classification step comprises the following steps:
[0120] SP B1 , Add 20 to 25 times the mass of distilled water to the grinding aid to dilute the grinding aid or make it into an emulsion for later use.
[0121] SP B2 , will be through SP A3 The crushed ore obtained in the step is evenly transported to the vertical mill, and a metering pump is used to transfer the SP B1The grinding aid treated in the step is sprayed onto the surface of the crushed ore in a mass ratio matched with the mass ratio of the conveyed crushed ore.
[0122] SP B3 , grinding the crushed ore added with the grinding aid by a vertical mill to obtain heavy calcium carbonate powder.
[0123] After the ground calcium carbonate powder is obtained by grinding, it needs to be classified, and the classification is completed under the cooperation of the coarse classifier 3, the trap 6, the fine classifier 10, the fine classifier 2 14 and the fine classifier 3 19. The upper part of the coarse classifier 3 is a cylindrical structure, the lower part is a conical structure, and the top is equipped with a classification drive device including a motor, a belt mechanism, etc.; the trap 6, the fine classifier 10, the fine classifier 2 14 and the fine classifier 3 19 are respectively cylindrical in the middle and conical in the upper and lower parts. The specific classification principle of each classifier is a well-known technology and will not be repeated here.
[0124] The coarse classifier 3 is provided with a powder conveying pipe 2, a powder recovery pipe 4 is provided at the bottom of the conical structure of the coarse classifier 3, a discharging motor is provided at one end of the powder recovery pipe 4 close to the coarse classifier 3, a powder conveying pipe 25 is provided at the other side of the upper part of the coarse classifier 3 near the top, the other end of the powder conveying pipe 25 is connected to one side of the top position of the cylindrical structure of the trap 6, the trap 6 is on one side of the powder conveying pipe 25, and an air supply pipe 1 is provided at the lower part of the cylindrical structure of the trap 6. A powder recovery pipe 27 is installed at the bottom of the lower conical structure of the trap 6, and a discharge motor is installed at one end of the powder recovery pipe 27 close to the trap 6. A powder conveying pipe 39 is installed at the top of the upper conical structure of the trap 6. The other end of the powder conveying pipe 39 is connected to one side of the top position of the cylindrical structure of the subdividing classifier 10. A powder recovery pipe 311 is installed at the bottom of the lower conical structure of the subdividing classifier 10. A discharge motor is installed at one end of the powder recovery pipe 311 close to the subdividing classifier 10. An air supply duct 28 is installed at the lower position of the cylinder near the first classifier 10, a powder conveying duct 4 13 is installed at the top of the conical structure of the subdividing classifier 10, and the other end of the powder conveying duct 4 13 is connected to one side of the top position of the cylindrical structure of the subdividing classifier 2 14, a powder recovery duct 4 15 is installed at the bottom of the conical structure of the subdividing classifier 2 14, and a discharging motor is installed at one end of the powder recovery duct 4 15 near the subdividing classifier 2 14, and an air supply duct 3 12 is installed at the lower position of the cylindrical structure of the subdividing classifier 2 14. A powder conveying pipe 5 17 is installed at the top of the conical structure of the subdividing classifier 2 14, and the other end of the powder recovery pipe 4 15 is connected to one side of the top position of the cylindrical structure of the subdividing classifier 3 19. A powder recovery pipe 5 20 is installed at the bottom of the conical structure of the subdividing classifier 3 19, and a discharge motor is installed at one end of the powder recovery pipe 5 20 close to the subdividing classifier 3 19. An air supply pipe 4 16 is installed at the lower position of the cylindrical structure of the subdividing classifier 3 19, and a powder conveying pipe 6 18 is installed at the top of the conical structure of the subdividing classifier 3 19. Sampling holes are opened at appropriate positions of the powder conveying pipe 2 5, the powder conveying pipe 3 9, the powder conveying pipe 4 13, the powder recovery pipe 4 15, and the powder conveying pipe 6 18.
[0125] SP B4During the grinding process, heavy calcium carbonate powder with trace amounts of large calcium carbonate particles is introduced into the coarse classifier 3 through the powder conveying pipe 2. The coarse classifier 3 separates the heavy calcium carbonate powder from the large calcium carbonate particles. The separated heavy calcium carbonate powder enters the trap 6 through the powder conveying pipe 5. The separated large calcium carbonate particles are returned to the vertical mill through the powder recovery pipe 4 for further grinding. Before the heavy calcium carbonate powder enters the trap 6, it is sampled online and the particle size is tested. Specifically, the sampling is performed online through the sampling hole provided on the powder conveying pipe 5. The grinding process parameters of the vertical mill are adjusted according to the test results until the particle size range of the ground heavy calcium carbonate powder is D 50 ≦1.55μm, D 97 ≦12.00μm.
[0126] SP B5 , particle size D 50 ≦1.55μm, D 97 The heavy calcium carbonate powder with a particle size of ≦12.00 μm enters the trap 6 through the powder conveying pipe 2 5 for classification. During the classification process in the trap 6, the sampling hole provided on the powder conveying pipe 3 9 is used to realize online sampling and particle size detection. The air flow rate introduced into the trap 6 through the air supply pipe 1 is adjusted according to the particle size detection result until the particle size of the classified heavy calcium carbonate powder is D 50 ≦1.55μm, D 97 ≦10.00μm. 50 ≦1.55μm, D 97 The heavy calcium carbonate powder with a particle size of ≦10.00 μm is introduced into the fine classifier 10 through the powder conveying pipeline 3 9, and the remaining heavy calcium carbonate powder after classification is introduced into the finished product warehouse. The heavy calcium carbonate powder introduced into the finished product warehouse is used as the production filler of pipes and rolled plates.
[0127] SP B6 The particle size of the particles introduced into the subdividing classifier 10 is D 50 ≦1.55μm, D 97 The heavy calcium carbonate powder with a particle size of ≦10.00 μm is further classified, and the sampling hole arranged on the powder conveying pipeline 4 13 is used to take samples online and detect the particle size, and the air flow introduced into the subdividing classifier 10 through the air supply pipeline 2 8 is adjusted until the particle size D is obtained. 50 ≦1.40μm, D 97 ≦6.00μm heavy calcium carbonate powder, particle size D 50 ≦1.40μm, D 97The heavy calcium carbonate powder with a particle size of ≦6.00 μm is continuously introduced into the second sub-classifier 14, and the remaining heavy calcium carbonate powder after classification is introduced into the finished product bin. The heavy calcium carbonate powder introduced into the finished product bin is used as a filler for modified plastics and rubber.
[0128] SP B7 The particle size introduced into the subdividing classifier 14 is D 50 ≦1.40μm, D 97 The heavy calcium carbonate powder with a particle size of ≦6.00 μm is further classified, and the sampling hole provided on the powder recovery pipeline 4 15 is used to take samples online and detect the particle size, and the air flow introduced into the subdividing classifier 2 14 through the air supply pipeline 3 12 is adjusted until the particle size D is obtained. 50 >1.15μm, D 97 >3.00μm calcium carbonate powder, D 50 >1.15μm, D 97 The heavy calcium carbonate powder with a particle size of more than 3.00 μm is continuously introduced into the fine classification machine 3 19 through the powder recovery pipe 4 15, and the remaining heavy calcium carbonate powder after classification is introduced into the finished product bin, and the heavy calcium carbonate powder introduced into the finished product bin is used for filling paint and ink.
[0129] SP B8 , the particle size D introduced into the subdivision classifier 3 19 50 >1.15μm, D 97 The heavy calcium carbonate powder with a particle size of >3.00 μm is further classified, and the sampling is performed online through the sampling hole arranged on the powder conveying pipeline 6 18 and the particle size is detected, and the air flow introduced into the subdividing classifier 3 19 through the air supply pipeline 4 16 is adjusted until the particle size of 1.25 μm≦D is classified. 50 ≦1.35μm, 3.80μm≦D 97 Heavy calcium carbonate powder ≦4.00μm. Particle size 1.25μm≦D 50 ≦1.35μm, 3.80μm≦D 97 The heavy calcium carbonate powder with a particle size of ≦4.00 μm is discharged through the powder conveying pipe 6 18 to become the heavy calcium carbonate powder used in this embodiment, and the remaining heavy calcium carbonate powder after classification is introduced into the finished product warehouse. The heavy calcium carbonate powder introduced into the finished product warehouse is used as a filler for plastic modification.
[0130] The purpose of using multiple classifications in this embodiment is to ensure that the particle size distribution of the heavy calcium carbonate powder used in silicone glue tends to the narrow particle size of light calcium carbonate (nano calcium carbonate), thereby ensuring the stability of the performance of the finished silicone glue.
[0131] The modification of the heavy calcium carbonate powder in this embodiment is prepared by using a zero-gravity mixer 1, a zero-gravity mixer 2 and two sets of metering pump metering feeding devices with a heater function, including the following steps:
[0132] SP C1 1. Heat the zero-gravity mixer to 90-95°C and keep it warm for 30 minutes; 2. Pass cooling water through the zero-gravity mixer.
[0133] SP C2 , placing the castor oil derivative into a heater of a metering pump metering feeding device for heating to reduce the viscosity of the castor oil derivative, and the heating temperature of the heater is controlled at 70-90°C.
[0134] SP C3 , heat the glycerin in another set of heaters of the metering pump metering feeding device to reduce the viscosity of the glycerin, and control the heating temperature of the heater at 50-60°C.
[0135] SP C4 , will be through SP B8 The heavy calcium carbonate powder prepared in the step is measured and poured into the zero-gravity mixer 1, and the zero-gravity mixer 1 is started to stir the heavy calcium carbonate powder. The stirring speed of the zero-gravity mixer 1 is 50 to 70 rad / min.
[0136] SP C5 2. Under the stirring state of the zero-gravity mixer, the dispersant weighed according to the ratio is evenly added into the zero-gravity mixer, and the adding time is controlled within 30 to 45 seconds.
[0137] SP C6 2. When the temperature of the heavy calcium carbonate powder mixed with the dispersant in the zero-gravity mixer reaches 90°C, the aluminate coupling agent weighed according to the ratio is evenly and slowly added into the zero-gravity mixer, and the adding time is controlled within 30 to 60 seconds.
[0138] SP C7 10 minutes after adding the aluminate coupling agent, C2 The castor oil derivative heated and reduced in viscosity is evenly sprayed into the zero-gravity mixer 1 by a metering pump metering feeding device, and the spraying time is controlled to be completed within 45 to 60 seconds.
[0139] SP C8 1 minute after the spraying of the castor oil derivative is completed, C3 The heated and viscosity-reduced glycerin is evenly sprayed into the zero-gravity mixer 1 by a metering pump metering feeding device, and the spraying time is controlled to be completed within 30 to 45 seconds.
[0140] SP C9 1 minute after the glycerol is sprayed, N,N′-ethylenebisstearamide weighed according to the ratio is evenly added into the zero-gravity activation machine 1, and the adding time is controlled to be completed within 30 to 45 seconds.
[0141] SP C10 , the zero-gravity mixer continues stirring and heating for 20 to 25 minutes.
[0142] SP C11 , evenly and slowly add the rheological agent weighed according to the ratio, the adding time is controlled to be completed within 45 to 60 seconds, and continue stirring for 3 to 5 minutes.
[0143] SP C12 , will be through SP C11 The material obtained by stirring in step 2 is discharged into the second weightless mixer and stirred at a speed of 50 to 70 rad / min until the material is cooled to room temperature to obtain modified heavy calcium carbonate.
[0144] SP C13 , using a natural density meter to measure the bulk density of the modified heavy calcium carbonate, the bulk density is ≤ 0.45 g / cm 3 The contact angle of the modified heavy calcium carbonate is measured by a contact angle meter, and the contact angle is ≧125°. The Hunter whiteness of the modified heavy calcium carbonate is measured by a whiteness meter, and the Hunter whiteness is ≧97%. The activation degree and oil absorption value of the modified heavy calcium carbonate are measured according to GB / T19281-2014 "Analysis Method of Calcium Carbonate", and the activation degree is ≧95%, and the oil absorption value is ≦12.5g / 100g. The modified heavy calcium carbonate is qualified.
[0145] SP C14 , the modified heavy calcium carbonate that passes the test is packaged into finished products.
[0146] There are two main purposes for heating the glycerol and the castor oil derivatives. On the one hand, they are to melt the solid solution in the above compounds; on the other hand, they are to reduce the viscosity of the glycerol and the castor oil derivatives so as to make them more evenly and quickly dispersed in the heavy calcium carbonate powder.
[0147] The reason for adding the dispersant first is that the particle size of the heavy calcium carbonate powder is too small, and adding it first can prevent the heavy calcium carbonate from agglomerating during the stirring process. The auxiliary agents are added in the order of the dispersant, the aluminate coupling agent, the castor oil derivative, the glycerol, the N,N'-ethylene bisstearamide, and the rheological agent for the following reasons:
[0148] ①Prevent mutual interference between different additives to avoid reducing the functions of the additives.
[0149] ② Maximize the functions of different additives, first ensure the dispersion of the heavy calcium carbonate powder by the dispersant, then ensure the coupling of the aluminate coupling agent to the heavy calcium carbonate powder, and consume the hydroxyl (-OH) on the surface of the calcium carbonate powder to the maximum extent, so as to ensure the hydroxyl (-OH) and amine (-NH 2 ), amide group (-CONH 2 ) is retained in order to form a more complete network structure.
[0150] ③ Prevent liquid additives from adhering to solid additives, thereby causing functional defects.
[0151] For the sake of simplicity, in the following examples:
[0152] ① The heavy calcium carbonate is exemplified by using a particle size of D 50 =1.30μm, D 97 =3.95μm;
[0153] ② In the following embodiments, since the grinding aid mainly affects the grinding efficiency, the amount of the grinding aid is 1.5‰ of the mass of the crushed ore for example;
[0154] ③ In the maleic ricinoleic acid polyethylene glycol ester, n is selected from 15 for example;
[0155] ④ In the polyetheramine grafted polycaprolactone comb-shaped hyperdispersant, m:n is selected as 1:0.7 for example;
[0156] ⑤ In the polyamide amine grafted polycaprolactone comb-shaped hyperdispersant, p is selected as 5 for example;
[0157] ⑥ The terminal amine polycaprolactone comb-shaped hyperdispersant n is selected as 13 for example.
[0158] Example 1
[0159] The grinding aid used for grinding is sodium methyl ricinoleate sulfonate.
[0160] The ratio of modified heavy calcium carbonate is: 100 parts of heavy calcium carbonate, 0.3 parts of N,N′-ethylenebisstearamide, 0.35 parts of glycerol, 0.8 parts of aluminate coupling agent, 1.0 parts of multifunctional castor oil-based polyurethane acrylate, 0.3 parts of polyetheramine grafted polycaprolactone comb-like hyperdispersant, and 0.8 parts of polyamide wax.
[0161] Example 2
[0162] The grinding aid used for grinding is sodium methyl ricinoleate sulfonate.
[0163] The ratio of modified heavy calcium carbonate is: 100 parts of heavy calcium carbonate, 0.3 parts of N,N′-ethylenebisstearamide, 0.2 parts of glycerol, 1.5 parts of aluminate coupling agent, 0.7 parts of multifunctional castor oil-based polyurethane acrylate, 0.7 parts of polyetheramine grafted polycaprolactone comb-like hyperdispersant, and 0.5 parts of polyamide wax.
[0164] Example 3
[0165] The grinding aid used for grinding is sodium methyl ricinoleate sulfonate.
[0166] The ratio of modified heavy calcium carbonate is: 100 parts of heavy calcium carbonate, 0.4 parts of N,N′-ethylenebisstearamide, 0.3 parts of glycerol, 1.2 parts of aluminate coupling agent, 0.85 parts of multifunctional castor oil-based polyurethane acrylate, 0.5 parts of polyetheramine grafted polycaprolactone comb-like hyperdispersant, and 0.65 parts of polyamide wax.
[0167] Example 4
[0168] The grinding aid used for grinding is sodium methyl ricinoleate sulfonate.
[0169] The ratio of modified heavy calcium carbonate is: 100 parts of heavy calcium carbonate, 0.5 parts of N,N′-ethylenebisstearamide, 0.35 parts of glycerol, 1.5 parts of aluminate coupling agent, 1.0 parts of multifunctional castor oil-based polyurethane acrylate, 0.7 parts of polyetheramine grafted polycaprolactone comb-like hyperdispersant, and 0.8 parts of polyamide wax.
[0170] Example 5
[0171] The grinding aid used for grinding is sodium methyl ricinoleate sulfonate.
[0172] The ratio of modified heavy calcium carbonate is: 100 parts of heavy calcium carbonate, 0.3 parts of N,N′-ethylenebisstearamide, 0.2 parts of glycerol, 0.8 parts of aluminate coupling agent, 0.7 parts of multifunctional castor oil-based polyurethane acrylate, 0.3 parts of polyetheramine grafted polycaprolactone comb-like hyperdispersant, and 0.5 parts of polyamide wax.
[0173] Example 6
[0174] The grinding aid used for grinding is sodium oleyl alcohol sulfonate.
[0175] The ratio of modified heavy calcium carbonate is: 100 parts of heavy calcium carbonate, 0.5 parts of N,N′-ethylenebisstearamide, 0.35 parts of glycerol, 1.5 parts of aluminate coupling agent, 1.0 parts of multifunctional castor oil-based polyurethane acrylate, 0.7 parts of polyetheramine grafted polycaprolactone comb-like hyperdispersant, and 0.8 parts of polyamide wax.
[0176] Example 7
[0177] The grinding aid used in the grinding process is sodium acrylate.
[0178] The ratio of modified heavy calcium carbonate is: 100 parts of heavy calcium carbonate, 0.5 parts of N,N′-ethylenebisstearamide, 0.35 parts of glycerol, 1.5 parts of aluminate coupling agent, 1.0 parts of multifunctional castor oil-based polyurethane acrylate, 0.7 parts of polyetheramine grafted polycaprolactone comb-like hyperdispersant, and 0.8 parts of polyamide wax.
[0179] Example 8
[0180] The grinding aid used for grinding is sodium methyl ricinoleate sulfonate.
[0181] The ratio of modified heavy calcium carbonate is: 100 parts of heavy calcium carbonate, 0.5 parts of N,N′-ethylenebisstearamide, 0.35 parts of glycerol, 1.5 parts of aluminate coupling agent, 1.0 parts of polyethylene glycol maleic ricinoleate, 0.7 parts of polyetheramine grafted polycaprolactone comb-like hyperdispersant, and 0.8 parts of polyamide wax.
[0182] Example 9
[0183] The grinding aid used for grinding is sodium methyl ricinoleate sulfonate.
[0184] The ratio of modified heavy calcium carbonate is: 100 parts of heavy calcium carbonate, 0.5 parts of N,N′-ethylenebisstearamide, 0.35 parts of glycerol, 1.5 parts of aluminate coupling agent, 1.0 parts of castor oil-based aqueous compound, 0.7 parts of polyetheramine grafted polycaprolactone comb-like hyperdispersant, and 0.8 parts of polyamide wax.
[0185] Example 10
[0186] The grinding aid used for grinding is sodium methyl ricinoleate sulfonate.
[0187] The ratio of modified heavy calcium carbonate is: 100 parts of heavy calcium carbonate, 0.5 parts of N,N′-ethylenebisstearamide, 0.35 parts of glycerol, 1.5 parts of aluminate coupling agent, 1.0 parts of epoxy castor oil, 0.7 parts of polyetheramine grafted polycaprolactone comb-like hyperdispersant, and 0.8 parts of polyamide wax.
[0188] Embodiment 11
[0189] The grinding aid used for grinding is sodium methyl ricinoleate sulfonate.
[0190] The ratio of modified heavy calcium carbonate is: 100 parts of heavy calcium carbonate, 0.5 parts of N,N′-ethylenebisstearamide, 0.35 parts of glycerol, 1.5 parts of aluminate coupling agent, 1.0 parts of multifunctional castor oil-based polyurethane acrylate, 0.7 parts of polyamide amine grafted polycaprolactone comb-like hyperdispersant, and 0.8 parts of polyamide wax.
[0191] Example 12
[0192] The grinding aid used for grinding is sodium methyl ricinoleate sulfonate.
[0193] The ratio of modified heavy calcium carbonate is: 100 parts of heavy calcium carbonate, 0.5 parts of N,N′-ethylenebisstearamide, 0.35 parts of glycerol, 1.5 parts of aluminate coupling agent, 1.0 parts of multifunctional castor oil-based polyurethane acrylate, 0.7 parts of terminal amine "comb-shaped" polycaprolactone hyperdispersant, and 0.8 parts of polyamide wax.
[0194] Embodiment 13
[0195] The grinding aid used for grinding is sodium methyl ricinoleate sulfonate.
[0196] The ratio of modified heavy calcium carbonate is: 100 parts of heavy calcium carbonate, 0.5 parts of N,N′-ethylenebisstearamide, 0.35 parts of glycerol, 1.5 parts of aluminate coupling agent, 1.0 parts of multifunctional castor oil-based polyurethane acrylate, 0.7 parts of polyetheramine grafted polycaprolactone comb-like hyperdispersant, and 0.8 parts of organic bentonite.
[0197] Embodiment 14
[0198] The grinding aid used for grinding is sodium methyl ricinoleate sulfonate.
[0199] The ratio of modified heavy calcium carbonate is: 100 parts of heavy calcium carbonate, 0.5 parts of N,N′-ethylenebisstearamide, 0.35 parts of glycerol, 1.5 parts of aluminate coupling agent, 1.0 parts of multifunctional castor oil-based polyurethane acrylate, 0.7 parts of polyetheramine grafted polycaprolactone comb-like hyperdispersant, and 0.8 parts of fumed silica.
[0200] Comparative Example 1
[0201] Comparative Example: SP A10 The particle size of the prepared particles is (Malvern particle size tester) 1.25μm≦D 50 ≦1.35μm, 3.80μm≦D 97 ≦4.00μm heavy calcium carbonate powder, the grinding aid is sodium methyl ricinoleate sulfonate.
[0202] Comparative Example 2
[0203] The grinding aid used for grinding is sodium methyl ricinoleate sulfonate.
[0204] The modified heavy calcium carbonate ratio is: 100 parts of heavy calcium carbonate, 0.5 parts of N,N′-ethylenebisstearamide, 1.5 parts of aluminate coupling agent, 0.7 parts of polyetheramine grafted polycaprolactone comb-like hyperdispersant, and 0.8 parts of polyamide wax, that is, glycerol and castor oil derivatives in the unused components.
[0205] Comparative Example 3
[0206] The grinding aid used for grinding is sodium methyl ricinoleate sulfonate.
[0207] The modified heavy calcium carbonate ratio is: 100 parts of heavy calcium carbonate, 0.5 parts of N,N′-ethylenebisstearamide, 0.35 parts of glycerol, 0.7 parts of polyetheramine grafted polycaprolactone comb-like hyperdispersant, and 0.8 parts of polyamide wax, that is, the castor oil derivative and aluminate coupling agent in the unused components.
[0208] Comparative Example 4
[0209] The grinding aid used for grinding is sodium methyl ricinoleate sulfonate.
[0210] The modified heavy calcium carbonate ratio is: 100 parts of heavy calcium carbonate, 0.5 parts of N,N′-ethylenebisstearamide, 0.35 parts of glycerol, 1.5 parts of aluminate coupling agent, 0.7 parts of polyetheramine grafted polycaprolactone comb-like hyperdispersant, and 0.8 parts of polyamide wax, that is, the castor oil derivative in the unused components.
[0211] Comparative Example 5
[0212] The grinding aid used for grinding is sodium methyl ricinoleate sulfonate.
[0213] The modified heavy calcium carbonate ratio is: 100 parts of heavy calcium carbonate, 0.5 parts of N,N′-ethylenebisstearamide, 1.0 parts of multifunctional castor oil-based polyurethane acrylate, 0.7 parts of polyetheramine grafted polycaprolactone comb-like hyperdispersant, and 0.8 parts of polyamide wax, that is, glycerin in the unused components.
[0214] The bulk density, contact angle, activation degree, Hunter whiteness and oil absorption value of calcium carbonate were tested for Examples 1 to 14 and Comparative Examples 1 to 5, respectively. The corresponding test data are shown in Tables 1 and 2.
[0215] Table 1 Main performance indicators of modified heavy calcium carbonate of Examples 1 to 10
[0216]
[0217] Table 2 Main performance indicators of modified heavy calcium carbonate of Examples 11 to 14 and Comparative Examples 1 to 5
[0218]
[0219] It can be seen from Table 1 and Table 2 that the minimum contact angle of Examples 1 to 14 reaches 128.5°, which is much higher than the 17° contact angle of Comparative Example 1, indicating that the surface properties of the modified heavy calcium carbonate powder have changed from hydrophilic to hydrophobic; the activation degrees are all above 95.5%, and the maximum oil absorption value is 12.3g / 100g. Compared with the oil absorption value of 36g / 100g and the activation degree of 0 in Comparative Example 1, there is a very significant improvement. Except for Examples 13 and 14, whose whiteness is 97.5%, which is equivalent to 97.7% in Comparative Example 1, the whiteness of the other examples is higher than that of Comparative Example 1, indicating that organic bentonite and fumed silica have a certain influence on the whiteness of the modified powder. As can be seen from Table 1, the technical indicators of the modified powder of Example 4 are the best.
[0220] Comparative Examples 2, 3, 4 and 5 are all based on the same N, N'-ethylenebisstearamide, dispersant (polyetheramine grafted polycaprolactone comb-shaped hyperdispersant) and rheological agent (polyamide wax) dosage as in Example 4, but the addition of glycerol, aluminate and castor oil derivative (multifunctional castor oil-based polyurethane acrylate) alone or in combination is changed (the dosage is the same as in Example 4). From the comparison between Example 4 and Comparative Examples 2, 3, 4 and 5, it can be seen that the performance of the modified heavy calcium carbonate powder when only some additives are used is lower than that of the examples, especially the bulk density (0.472 g / cm2) of Comparative Example 3 without using castor oil derivatives and aluminate coupling agents is lower than that of the examples. 3 ), contact angle (35.5°), activation degree (26.8%) and oil absorption value (19.5g / 100g).
[0221] The silicone adhesives prepared in the above Examples 1 to 14 and Comparative Examples 2 to 5 are compared. Preparation of silicone adhesive:
[0222] ① Base material preparation
[0223] Put 825g of 107 glue and 150g of dimethyl silicone oil into a Z-type kneader, heat and stir for 30min, and add the mixture prepared in step SP C12 1890 g of the prepared modified heavy calcium carbonate powder was heated to 110-120 ° C, vacuumed and stirred for 3 h, the vacuum degree was maintained below -0.08 MPa, vented, 135 g of white oil was added, and stirring was continued for 30 min. It was cooled to room temperature to form a base material. Samples were taken and sealed under nitrogen protection. The consistency and viscosity of the base material were tested after being placed at room temperature of 23 ° C ± 0.5 ° C for not less than 24 h.
[0224] ② Preparation of silicone glue
[0225] Under nitrogen protection, 1000g of the base material was taken out from the Z-type kneader, put into a double-shaft planetary mixer, 50g of methyl tributylacetoximate silane and 5g of vinyl tributylacetoximate silane were added, and the mixture was stirred under vacuum for 30min, with the vacuum degree maintained below -0.08MPa. Then, 0.8g of dibutyltin dilaurate, 3g of KH550 (3-aminopropyltriethoxysilane) and 3g of KH560 (γ-glycidyloxypropyltrimethoxysilane) were added, and the mixture was stirred under vacuum for 25min. The mixture was extruded and poured into a rubber cartridge.
[0226] ③Silicone adhesive test
[0227] The viscosity of the base material was tested using a rotational viscometer;
[0228] The consistency of the base material is measured using a consistency tester;
[0229] Thixotropic index test: Place the rubber at room temperature of 23℃±0.5℃ for no less than 24h, and use a rotational viscometer to test it. Set the rotor speed to 5.6rad / min and 65rad / min, and measure the viscosity (η) of the silicone rubber. According to the formula n=η 5.6 / η 65 The other properties are tested according to the test methods specified in GB / T 14683-2017 “Silicone and modified silicone building sealants”. The test data are shown in Table 3 and Table 4.
[0230] Table 3 Performance test data of silicone glue filled with modified heavy calcium carbonate using Examples 1 to 9
[0231]
[0232] Table 4 Performance test data of silicone glue filled with modified heavy calcium carbonate using Examples 1 to 9 and Comparative Examples 1 to 5
[0233]
[0234]
[0235] It can be seen from Table 3 and Table 4 that the silicone adhesives prepared in Examples 1 to 14 all meet the requirements of GB / T 14683-2017 "Silicone and Modified Silicone Building Sealant" that the extrudability is ≧150ml / min, the sag is ≦3mm, the elastic modulus is >0.4MPa (23℃, high modulus), and the elastic recovery rate is ≧80%. The reason is that: on the one hand, the auxiliary agent glycerol, aluminate coupling agent, and castor oil derivative contain hydroxyl (-OH), alkoxy (-OR), amine (-NH 2 ), epoxy The glycerol, the castor oil derivative, and the dispersant are all long-chain macromolecular additives, and contain hydroxyl (-OH) or amine (-NH 2 ), when it is dissolved in an organic system, it gels due to hydrogen bonding to form a thixotropic network structure, and the long chains are swollen and entangled with each other. The rheological agent contains hydroxyl (-OH) and / or amide (-CONH 2 ), the molecules form a network structure due to the strong hydrogen bonding effect. These network structures or the intertwined long chains are destroyed under the action of shear force, which is manifested as a decrease in viscosity and the system recovers good fluidity. When the shear force is eliminated, the three-dimensional structure will recover by itself and the viscosity will increase, which is manifested as thixotropy; thirdly, the mutual use of composite additives forms a hydrophobic oil film on the surface of the heavy calcium carbonate. At the same time, the use of the N,N'-ethylene bisstearamide, glycerol, castor oil derivatives and dispersants separates the distance between the particles of the heavy calcium carbonate powder, so that when the modified heavy calcium carbonate of the present invention is used in the production of silicone glue, it has the excellent dispersibility and good extrusion property of the heavy calcium carbonate powder.
[0236] The description of the present invention is given for the purpose of illustration and description, and is not intended to be exhaustive or to limit the invention to the disclosed form. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for particular uses.
Claims
1. Modified calcium carbonate powder used in silicone adhesive, characterized by: It comprises heavy calcium carbonate powder and an additive for modifying the heavy calcium carbonate powder; The additives include N,N′-ethylenebisstearamide, glycerol, an aluminate coupling agent, a castor oil derivative, a dispersant and a rheological agent; The mass ratio of the heavy calcium carbonate powder and the additive is: 100 parts of the heavy calcium carbonate, 0.3-0.5 parts of the N,N′-ethylenebisstearamide, 0.2-0.35 parts of the glycerol, 0.8-1.5 parts of the aluminate coupling agent, 0.7-1.0 parts of the castor oil derivative, 0.3-0.7 parts of the dispersant, and 0.5-0.8 parts of the rheological agent.
2. The modified calcium carbonate powder for silicone adhesive according to claim 1, characterized in that: The castor oil derivative is one of maleic ricinoleic acid polyethylene glycol ester, castor oil-based water-based compound, multifunctional castor oil-based polyurethane acrylate, and epoxy castor oil; Wherein, the structural formula of the maleic ricinoleic acid polyethylene glycol ester is, Where n is 10, 15 or 20; The structural formula of the castor oil-based aqueous compound is, The structural formula of the multifunctional castor oil-based polyurethane acrylate is: The structural formula of the epoxy castor oil is:
3. The modified calcium carbonate powder for silicone adhesive according to claim 1, characterized in that: The dispersant is a comb-shaped hyperdispersant; The comb-shaped hyperdispersant is one of a polyetheramine grafted polycaprolactone comb-shaped hyperdispersant, a polyamideamine grafted polycaprolactone comb-shaped hyperdispersant, and an amine-terminated "comb-shaped" polycaprolactone hyperdispersant; Wherein, the structural formula of the polyetheramine grafted polycaprolactone comb-shaped hyperdispersant is: Where m:n is 1:0.7 or 1:0.8; The structural formula of the polyamidoamine grafted polycaprolactone comb-shaped hyperdispersant is: Where p is 5, 10 or 15; The structural formula of the amine-terminated "comb-shaped" polycaprolactone hyperdispersant is: Where n is 12 to 25.
4. The modified calcium carbonate powder for silicone adhesive according to claim 1, characterized in that: The rheological agent is one of polyamide wax, organic bentonite, and fumed silica, or a combination of the two in any ratio.
5. The method for preparing modified calcium carbonate powder for silicone adhesive according to claim 1, characterized in that: The method comprises the steps of processing and crushing the calcium carbonate ore raw material, grinding and classifying, online particle size detection, powder modification and modified powder inspection.
6. The preparation method according to claim 5, characterized in that: The processing and crushing steps include, SP A1 , Cleaning of ore raw materials The calcium carbonate ore raw material is washed with tap water to remove the silt and humus in the ore raw material; SP A2 , Sorting of ore raw materials Manually sort out and remove the miscellaneous colored ores that affect the white hue in the ore raw materials; SP A3 , Crushing of ore raw materials The ore raw materials are crushed by a jaw crusher, and after two consecutive crushing processes, the ore raw materials are crushed into crushed ore with a maximum size not exceeding 30mm.
7. The preparation method according to claim 6, characterized in that: In the grinding and classification step, the crushed ore is ground by a vertical grinding mill, and a grinding aid of 1 to 1.5‰ of the mass of the crushed ore is added during the grinding to obtain heavy calcium carbonate powder; The grinding aid is one of sodium methyl ricinoleate sulfonate, sodium oleyl alcohol sulfonate and sodium acrylate; The particle size of the heavy calcium carbonate powder tested by Malvern particle size tester is D 50 ≦1.55μm, D 97 ≦12.00μm.
8. The preparation method according to claim 7, characterized in that: The heavy calcium carbonate powder is classified, and the particle size of the heavy calcium carbonate powder selected after classification is 1.25 μm≦D tested by Malvern particle size tester. 50 ≦1.35μm, 3.80μm≦D 97 ≦4.00μm.
9. The preparation method according to claim 8, characterized in that: The grinding and classification step comprises the following steps: SP B1 1. Add 20 to 25 times the mass of distilled water to the grinding aid to dilute the grinding aid or make the grinding aid into an emulsion for standby use; SP B2 , will be through SP A3 The crushed ore obtained in the step is evenly transported to the vertical mill, and a metering pump is used to transfer the SP B1 The treated grinding aid is sprayed onto the surface of the crushed ore in a mass ratio matching the mass ratio of the conveyed crushed ore; SP B3 2. Grinding the crushed ore with grinding aid added by a vertical mill to obtain heavy calcium carbonate powder; SP B4 During the grinding process, the heavy calcium carbonate powder with large calcium carbonate particles enters the coarse classifier, and the coarse classifier separates the heavy calcium carbonate powder from the large calcium carbonate particles. The separated heavy calcium carbonate powder enters the trap, and the separated large calcium carbonate particles return to the vertical mill for further grinding; the heavy calcium carbonate powder is sampled online before entering the trap and the particle size is detected, and the grinding process parameters of the vertical mill are adjusted according to the detection results until the particle size range of the ground heavy calcium carbonate powder is D 50 ≦1.55μm, D 97 ≦12.00μm; SP B5 , particle size D 50 ≦1.55μm, D 97 The heavy calcium carbonate powder with a particle size of ≦12.00 μm enters the trap for classification, online sampling is performed for particle size detection, and the air flow introduced into the trap is adjusted until the particle size of the classified heavy calcium carbonate powder is D 50 ≦1.55μm, D 97 ≦10.00μm, the particle size is D 50 ≦1.55μm, D 97 Heavy calcium carbonate powder with a particle size of ≦10.00μm is introduced into the first fine-grained classifier, and the remaining heavy calcium carbonate powder after classification is introduced into the finished product bin. The heavy calcium carbonate powder introduced into the finished product bin is used as a filler in the production of pipes and rolled plates; SP B6 , the particle size introduced into the subdivision classifier is D 50 ≦1.55μm, D 97 The heavy calcium carbonate powder with a particle size of ≦10.00μm is further classified, and online sampling is performed for particle size detection, and the air flow rate introduced into the subdivision classifier is adjusted until the particle size D is obtained. 50 ≦1.40μm, D 97 ≦6.00μm heavy calcium carbonate powder, particle size D 50 ≦1.40μm, D 97 Heavy calcium carbonate powder with a particle size of ≦6.00μm is continuously introduced into the second sub-classifier, and the remaining heavy calcium carbonate powder after classification is introduced into the finished product bin. The heavy calcium carbonate powder introduced into the finished product bin is used as filler for modified plastics and rubber; SP B7 , the particle size introduced into the second subdivision classifier is D 50 ≦1.40μm, D 97 The heavy calcium carbonate powder with a particle size of ≦6.00μm continues to be classified, and online sampling is performed for particle size detection, and the air flow rate introduced into the second sub-classifier is adjusted until the particle size D is obtained. 50 >1.15μm、D 97 >3.00μm calcium carbonate powder, D 50 >1.15μm, D 97 Heavy calcium carbonate powder with a particle size of >3.00μm is continuously introduced into the third sub-classifier, and the remaining heavy calcium carbonate powder after classification is introduced into the finished product bin. The heavy calcium carbonate powder introduced into the finished product bin is used for filling paint and ink; SP B8 , the particle size D 50 >1.15μm, D 97 The heavy calcium carbonate powder with a diameter of >3.00μm continues to be classified, and online sampling is performed for particle size detection, and the air flow rate introduced into the subdivision classifier 3 is adjusted until the particle size of the classified powder is 1.25μm≦D 50 ≦1.35μm, 3.80μm≦D 97 Heavy calcium carbonate powder ≦4.00μm, the remaining heavy calcium carbonate powder after classification is introduced into the finished product warehouse, and the heavy calcium carbonate powder introduced into the finished product warehouse is used as filler for plastic modification.
10. The preparation method according to claim 9, characterized in that: The modification of the heavy calcium carbonate powder is prepared by using a first weightless mixer, a second weightless mixer and two sets of metering pump metering feeding devices with heater functions, including the following steps: SP C1 , raising the temperature of the zero-gravity mixer to 90-95° C. and keeping the temperature for 30 minutes; passing cooling water through the zero-gravity mixer; SP C2 , placing the castor oil derivative in a heater of a metering pump metering feeding device to heat the castor oil derivative to reduce the viscosity of the castor oil derivative, and the heating temperature of the heater is controlled at 70-90° C.; SP C3 , heating the glycerin in a heater of another set of the metering pump metering feeding device to reduce the viscosity of the glycerin, and controlling the heating temperature of the heater to be 50-60° C.; SP C4 , will be through SP B8 The heavy calcium carbonate powder prepared in the step is measured and poured into the zero-gravity mixer 1, and the zero-gravity mixer 1 is started to stir the heavy calcium carbonate powder, and the stirring speed of the zero-gravity mixer 1 is 50-70 rad / min; SP C5 , while the zero-gravity mixer is stirring, uniformly adding the dispersant weighed according to the ratio into the zero-gravity mixer, and the adding time is controlled within 30 to 45 seconds; SP C6 2. When the temperature of the heavy calcium carbonate powder mixed with the dispersant in the zero-gravity mixer 1 reaches 90° C., the aluminate coupling agent weighed according to the ratio is evenly and slowly added into the zero-gravity mixer 1, and the adding time is controlled within 30 to 60 seconds; SP C7 10 minutes after adding the aluminate coupling agent, C2 The castor oil derivative heated and reduced in viscosity is uniformly sprayed into the zero-gravity mixer 1 by using the metering pump metering feeding device, and the spraying time is controlled to be completed within 45 to 60 seconds; SP C8 1 minute after the spraying of the castor oil derivative is completed, C3 The heated and viscosity-reduced glycerin is uniformly sprayed into the zero-gravity mixer 1 by using the metering pump metering feeding device, and the spraying time is controlled to be completed within 30 to 45 seconds; SP C9 1 minute after the glycerol is sprayed, N,N′-ethylenebisstearamide weighed according to the ratio is uniformly added into the zero-gravity activation machine 1, and the adding time is controlled to be completed within 30 to 45 seconds; SP C10 , the zero-gravity mixer continues stirring and heating for 20 to 25 minutes; SP C11 , uniformly and slowly add the rheological agent weighed according to the ratio, the adding time is controlled to be completed within 45 to 60 seconds, and continue stirring for 3 to 5 minutes; SP C12 , will be through SP C11 The material obtained by stirring in step 2 is discharged into the second weightless mixer, and stirred at a speed of 50 to 70 rad / min until the material is cooled to room temperature to obtain modified heavy calcium carbonate; SP C13 , using a natural density meter to measure the bulk density of the modified heavy calcium carbonate, the bulk density is ≤ 0.45 g / cm 3 The contact angle of the modified heavy calcium carbonate is measured by a contact angle meter, and the contact angle is ≧125°. The Hunter whiteness of the modified heavy calcium carbonate is measured by a whiteness meter, and the Hunter whiteness is ≧97%. The activation degree and oil absorption value of the modified heavy calcium carbonate are measured according to GB / T19281-2014 "Analysis Method of Calcium Carbonate", and the activation degree is ≧95%, and the oil absorption value is ≦12.5g / 100g. The modified heavy calcium carbonate is qualified; SP C14 , the modified heavy calcium carbonate that passes the test is packaged into finished products.
Citation Information
Patent Citations
Preparation method of nanometer calcium carbonate used for silicone adhesive
CN108913058A
A method for preparing heavy calcium carbonate for high-activation silicone sealant
CN113088102B
Preparation method of nano calcium carbonate for flame-retardant silicone sealant
CN116282114A
Cited By
Modified silane coupling agent, modified heavy calcium carbonate, dealcoholized silicone sealant and preparation method thereof
CN121554497A